Arsenic Species in Cordyceps sinensis and Its Potential Health Risks - Li, Yaolei; Liu, Yue; Han, Xiao; Jin, Hongyu; Ma, Shuangcheng (Frontiers in Pharmacology, 2019)
High arsenic residues make Cordyceps sinensis a concern in China. Arsenic toxicity is related to its species. Many studies have evaluated the toxicity of total arsenic, but few have studied its species. In this study, the species of arsenic in C. sinensis and its potential health risk were investigated. SEC-HPLC-ICP-MS was used to analysis of arsenic in C. sinensis and unknown arsenic (uAs) was discovered. Additionally, arsenic in C. sinensis was mainly found in alkali-soluble proteins. The trend of arsenic transformation indicated that unknown arsenic in C. sinensis may be converted into free inorganic arsenic, which enhanced toxicity. The result of risk assessment indicated that there were potential health risks of uAs. Hereon, we proposed recommendations for the use of C. sinensis and regulatory recommendations for arsenic standards. This study contributed to the toxicity reveal, safety evaluation, and risk assessment of arsenic in C. sinensis.